Effects of a supply chain regulation: Survey-based results on the expected effects of the German Supply Chains Act - Galina V. Kolev; Adriana Neligan (Institut der deutschen Wirtschaft (IW), 2022)
The European Commission is planning a new regulation for mandatory human rights and environmental due diligence (Due Diligence Directive) as part of the Sustainable Corporate Governance initiative. The longawaited EU proposal is expected to have requirements that go far beyond the German Act on Due Diligence in Supply Chains (the so-called Lieferkettensorgfaltspflichtengesetz), which was regarded as a possible blueprint for a European solution. The present paper contributes to the debate on an EU due diligence regulation by presenting results of a recent survey conducted by the German Economic Institute (IW) on the potential impact of the already adopted German Act on Due Diligence in Supply Chains. It highlights both the positive effects and the undesirable side effects in the form of adjustments to value chains, product prices, etc. that German companies expect from the introduction of this German regulation. The results from the survey indicate that the introduction of a due diligence regulation is costly and should also consider the expected negative effects. The high costs of compliance are likely to motivate many companies to withdraw their activity from (mostly developing) countries with weak governance with devastating consequences for the jobs they created in the past, the production standards they brought and the capital they invested. Therefore, the new EU regulation should be carefully introduced and only target companies where evidence is available about misuse of weak production standards in third countries. It is important that the level of regulation by no means is higher than the level of regulation by the German Act on Due Diligence in Supply Chains.
Keywords: F18; Q56; Q01; 330